Hepatic fibrogenesis and transforming growth factor/Smad signaling activation in rats chronically exposed to low doses of lead - Pérez Aguilar, Rossana Cristina (2013)
Lead is an important heavy metal pollutant in the environment. The nervous system, kidney and liver are the most susceptible organs to lead deposition, showing that this pollutant has no single target system. To examine the cellular and molecular mechanisms involved in their pathobiology of chronic lead at low-dose exposure in the liver, male Wistar rats were exposed to 0.06% lead acetate in drinking water every day for 4 months. At the end of the study, hepatic metal accumulation, morphology and function were examined. Immunochemical staining and Western blot analysis were performed to detect extracellular matrix proteins, α-smooth muscle actin and transforming growth factor (TGF)β1/Smad pathway expression. Results showed increased laminin, collagen IV and fibronectin, located at the perisinusoidal space. Phenotypic transformation of hepatic stellate cells into myofibroblast-like cells was evidenced at the ultrastructural level and a significant expression of α-smooth muscle actin in Disse's space was observed. These findings were associated with a marked increase in TGFβ1/Smad2/3 signaling. Our data suggest that, chronically, exposure to low levels of lead could trigger the onset of a hepatic fibrogenic process through upregulated TGFβ1/Smad signaling.